Embarazo ectópico ovárico, reporte de un caso y revisión bibliográfica - Bustamante A., Emilio; Castillo M., Carlos; Alarcón V., Felipe; Venegas N., Marcia; Zuñiga I., Leonardo (Revista Hospital Clínico Universidad de Chile, 2015)
Ovarian pregnancy is a rare event. Its prevalence varies from one in 2100 to one in 60000 pregnancies, corresponding to 1-3% of ectopic pregnancies. The diagnosis is a challenge for the clinician, and without adequate resources can be a surgical finding. This article reports the case of a 30 years old woman attended in our hospital with pregnancy as diagnosis, who consulted because of three days of vaginal bleeding and abdominal pain. Ultrasonography showed a tubaric ring with a gestational sac inside, and an embryo with detectable heartbeats. A laparotomy was performed and an embryo around 6 weeks old located in the right ovary was extracted. The patient was discharged from the hospital 2 days after the surgery with a satisfactory evolution.